Increasing Rhythmic Gymnastics Skills in Students Through M-Gym Media - Eva Faridah,; Indra Kasih,; Sinung Nugroho,; Esi Emilia, (Technium Social Sciences Journal, 2024)
The purpose of this study was to determine whether M-Gym media could help students improve their rhythmic gymnastics skills. This study was based on Borg and Gall's research. This study was planned at Universitas Negeri Medan's Faculty of Sports Science. Meanwhile, this study was carried out for one semester, from April 2nd to April 29th, 2024. The findings of this study revealed that in the small class trial, 70% of the students' rhythmic activity abilities were evaluated as weak during the pretest stage. The test was performed on students before they begin learning with m-gym media. However, when students in small classes were taught with m-gym media, their results were different. The majority of students (83.3%) have good rhythmic abilities. In the large class trial, the majority of students' rhythmic activity abilities were rated as inadequate at the pretest stage, 56%. The test was performed on students before they begin learning with M-Gym media. However, when students in big classes were taught utilizing M-Gym media, the results were different. Most students are proficient in rhythmic gymnastics. The conclusion showed that students could perform fundamental rhythmic activity motions correctly when provided directions during learning utilizing M-Gym media.